2020
DOI: 10.3390/metabo10100382
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Reproducibility of Plasma Metabolomic Biomarkers of Habitual Food Intake in a US Diet Validation Study

Abstract: Previous metabolomic studies have identified putative blood biomarkers of dietary intake. These biomarkers need to be replicated in other populations and tested for reproducibility over time for the potential use in future epidemiological studies. We conducted a metabolomics analysis among 671 racially/ethnically diverse men and women included in a diet validation study to examine the correlation between >100 food groups/items (101 by a food frequency questionnaire (FFQ), 105 by 24-h diet recalls (24HRs)) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 42 publications
(82 reference statements)
5
15
0
Order By: Relevance
“…Reproducibility of the 513 unique metabolites over six months was good for a large proportion, with 28% of metabolites with an ICC > 0.6. The comparisons of urinary dietary biomarkers identified in the present study with our previous findings in fasting plasma samples in the same study [13] revealed several overlapping food biomarkers identified in both blood and urine and many more putative biomarkers identified in urine for further evaluation. This study also provided important information on the reproducibility of the urinary biomarkers, which could facilitate their utilization in future clinical and epidemiological studies.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…Reproducibility of the 513 unique metabolites over six months was good for a large proportion, with 28% of metabolites with an ICC > 0.6. The comparisons of urinary dietary biomarkers identified in the present study with our previous findings in fasting plasma samples in the same study [13] revealed several overlapping food biomarkers identified in both blood and urine and many more putative biomarkers identified in urine for further evaluation. This study also provided important information on the reproducibility of the urinary biomarkers, which could facilitate their utilization in future clinical and epidemiological studies.…”
Section: Discussionsupporting
confidence: 67%
“…Several large metabolomics analyses conducted in cohort studies employing a cross-sectional study design have identified hundreds of potential biomarkers of habitual food intakes [6][7][8][9][10][11][12][13] or dietary patterns [14,15]. Our previous metabolomics analyses of blood samples from the Cancer Prevention Study-II (CPS-II) Nutrition Cohort [6] and CPS-3 [13] have identified more than 200 putative food-related metabolic markers, many of which replicated findings from other population and feeding studies. The most common metabolite class was xenobiotics, which were highly correlated with plant foods.…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations